PENGEMBANGAN MATERI AJAR KETERAMPILAN BERBAHASA JAWA RESEPTIF BERBASIS UNGKAPAN TRADISIONAL SEBAGAI MEDIA PENDIDIKAN KARAKTER - Esti Sudi Utami; Teguh Supriyanto (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2015)
AbstractThis study aims to develop traditional-expression-based learning materials for Javanesereceptive skills as character education media for junior high school (JHS) students. Thiswas a research and development study. The research product was a model of learningmaterials relevant to Javanese learning needs at JHS. The developed learning materialswere in the form of story discourses entitled proverbs containing character values. Thelearning materials were packed in an anthology of short stories and a short movie CD usingJavanese of the ngapak [a], Surakarta [û], dan Pati [ m] dialects. The learning materials forthe [a] dialect were used at JHSs in the areas around Kebumen and Pekalongan. Those forthe [û] dialect were used in the areas around Surakarta, Salatiga, and Semarang. Thosefor the [ m] dialect were used in the areas around Pati and Blora. The results of the productevaluation showed that the products were good with scores of 4.35 for the book and 4.50for the short movie CD. The model of the materials could be used as media to improvereceptive skills and inculcate values through character education into students.